2021
DOI: 10.1002/tpg2.20157
|View full text |Cite
|
Sign up to set email alerts
|

Genomic prediction modeling of soybean biomass using UAV‐based remote sensing and longitudinal model parameters

Abstract: The application of remote sensing in plant breeding can provide rich information about the growth processes of plants, which leads to better understanding concerning crop yield. It has been shown that traits measured by remote sensing were also beneficial for genomic prediction (GP) because the inclusion of remote sensing data in multitrait models improved prediction accuracies of target traits. However, the present multitrait GP model cannot incorporate high‐dimensional remote sensing data due to the difficul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…Nevertheless, this study has shown that GF is a useful trait to describe the growth of soybean germplasm. In genomic prediction, the inclusion of canopy area, which is proportional to GF, has been reported to improve the prediction of biomass in soybean ( Toda et al, 2021a ). Thus, GF can be considered a useful index of genetic variation in plant growth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, this study has shown that GF is a useful trait to describe the growth of soybean germplasm. In genomic prediction, the inclusion of canopy area, which is proportional to GF, has been reported to improve the prediction of biomass in soybean ( Toda et al, 2021a ). Thus, GF can be considered a useful index of genetic variation in plant growth.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the GP model is applied to predict the parameters of the GF dynamics model under a range of scenarios to illustrate the potential of the proposed method. A similar experiment was conducted in an earlier paper in which UAV-RS data was used as secondary traits to predict biomass ( Toda et al, 2021a ), while this study developed prediction models of growth curve itself.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, this study has shown that GF is a useful trait to describe the growth of soybean germplasm. In genomic prediction, the inclusion of canopy area, which is proportional to GF, has been reported to improve the prediction of biomass in soybean (Toda et al, 2021). Thus, GF can be considered a useful index of genetic variation in plant growth.…”
Section: Uav-rs As a Tool To Evaluate Growth Patternsmentioning
confidence: 99%
“…Many time-series models have been proposed for analyzing crop phenology. Such models include shape-model fitting (Sakamoto et al, 2013;Zhou et al, 2020), random regression with the Legendre polynomial (Campbell et al, 2018;Campbell et al, 2019), segmented linear regression (Toda et al, 2021), and non-linear growth curves (Chang et al, 2017;Grados et al, 2020;Poudel et al, 2022). Anderson et al (2019) applied a three-parameter logistic model (S-shape non-linear curve) to maize CH time-series data measured by UAV over 1 year, applied a linear mixed effects (LME) model to the logistic parameters, decomposed the parameter variance into genetic and environmental effects: they showed that some of the parameters could be used as predictors of grain yield.…”
Section: Introductionmentioning
confidence: 99%
“…Many time-series models have been proposed for analyzing crop phenology. Such models include shape-model fitting ( Sakamoto et al., 2013 ; Zhou et al., 2020 ), random regression with the Legendre polynomial ( Campbell et al., 2018 ; Campbell et al., 2019 ), segmented linear regression ( Toda et al., 2021 ), and non-linear growth curves ( Chang et al., 2017 ; Grados et al., 2020 ; Poudel et al., 2022 ). Anderson et al.…”
Section: Introductionmentioning
confidence: 99%